Women's Right and Alternative Solutions to Prevent Violence for Muslim Marriage Dispensation Couples in Ponorogo - Indah Fatmawati; Ritus Nur Armada; Agustinus Astono (Institut Agama Islam Negeri Ponorogo, 2025)
Of the many cases of dispensation from marriage, it is known that the bride-to-be is already pregnant, while the man as the groom-to-be is willing to marry for responsible reasons. Of course, this is considered morally right, but if viewed from a gender perspective, even if the marriage takes place, a series of accompanying problems will arise, including divorce, violence and gender injustice against women. From the data that the researchers found at the Religious Court class 1A in Ponorogo Regency, from 2021 to 2022 there were 345 cases of dispensation of marriage, of which more than 125 cases were filed because the prospective bride was pregnant. Furthermore, from the reports of the Women and Children Protection Unit (PPA) POLRES Ponorogo, it was also found that there were approximately 9 cases of violence against female partners who did dispensation of marriage. This is certainly interesting to study considering the cases that occurred showed that there was both physical and sexual violence that occurred in underage marriages. This study aims to examine women's rights by looking at the role of men and alternative solutions in preventing acts of violence against women in marriage dispensation couples with a gender perspective. Furthermore, the research was carried out by interviews and direct observation and also supported by existing secondary data. From this research, it can be concluded that the role of men must be taken into account by being responsible for marrying the woman they are pregnant with in preventing violence, while alternative solutions must continue to be actualized by maximizing the role of stakeholders in preventing violence against women.